MEMPERKUAT PAHAM MODERASI BERAGAMA DALAM MENANGKAL NARASI KEBENCIAN DI MEDIA SOSIAL - Hamam Burhanuddin; Fahmi Khumaini (Ta'allum: Jurnal Pendidikan Islam, 2021)
The stigma of thoughts and movements to be radical and smells of violence still surrounds life in Indonesia, this is behind the importance of moderate Islamic thought by "Islam wasatiyah". This paper explain about strengthening religious moderation to counter hate narratives on social media. The study in this paper is qualitative. The conceptual framework offered uses a constructivist paradigm where technology seen as a product of social construction. The agent-structure approach is base on Giddens' theory of structuration. The technology studied is social media technology, while the agent in question is a social media user, then communication culture is place as a social structure that acts as a wider context. The conceptual framework as described here is especially useful for describing the relationship between technology and society and answering the question of how the interplay between technology and social behavior occurs in society.